Analysis Study for Rabobank Group ICT Incident by using Fuzzy and Heuristic Miner in Process Mining - Andreswari, Rachmadita; Millenia, Frista; Rizky, Juan; Haniyah, Salma; Mufti, Shofian (Iraqi Journal for Electrical and Electronic Engineering, 2023)
The decline in the marketing volume of Rabobank Group ICT is a serious incident as it can hinder the implementation of an increasing number of software releases for business development. The Service Desk Agent records the activities that occur to find out the problems experienced in the form of an event log. Process mining can be used to generate process model visualizations based on event logs to explicitly monitor the business. Fuzzy Miner and Heuristic Miner algorithms can be used to handle complex event logs. In this study, an analysis of the Rabobank Group ICT incident was carried out with process mining using the Fuzzy Miner and Heuristic Miner algorithms. Process mining is done by discovery, conformance, and enhancement. Based on the results of the study, it is known that the division of the work area is not good enough to cause a team to work on a lot of events while there are other teams that only work on one event. Therefore, it is necessary to have a clear and balanced division of domains and workloads so that incidents do not recur.